(untitled) (Vietnam Journal of Community Medicine, 2026)
Cutaneous larva migrans is a common condition in tropical and subtropical regions, most commonly caused by the larvae of nematodes. The disease is characterized by serpiginous, erythematous, and pruritic skin lesions resulting from the penetration and migration of larvae within the skin. This article reports a case of a 2-year-old male child living in Thu Dau Mot, Ho Chi Minh City, who presented with a serpiginous erythematous skin lesion resembling cutaneous larva migrans and was admitted to the Infectious Diseases Department of the University Medical Center Ho Chi Minh City. The lesion was approximately 3.5 cm in length, with a short black segment observed at one end. Histopathological examination and microscopic analysis demonstrated that the lesion was not caused by parasitic larvae but by an embedded human hair fragment. Hair fragments penetrating the skin may produce a variety of clinical manifestations, among which the most distinctive presentation closely mimics cutaneous larva migrans. Clinicians should carefully examine patients and analyze specimens to ensure accurate diagnosis and timely management.